The Influence of Orientalist Thought on the Paradigm of Modern Islamic Education: A Critical Study from Edward Said's Perspective - Muhammad Hudhel Sidqi; Febriyanti Ghayatul Qushwa; Bakri Muhammad Bakhiet (Center of Islamic and Occidental Studies, 2025)
Motivated by an epistemological crisis in modern Islamic education caused by secular and positivist Orientalist thought, this research examines how this paradigm shapes educational perspectives, systems, and curricula. Using qualitative analysis of relevant literature, the study identifies three key channels of Orientalist influence: curriculum design, academic language, and the criteria for scientific legitimacy. The research also highlights the counter-paradigm offered by Muslim intellectuals such as Syed M. Naquib al-Attas, Ismail Raji al-Faruqi, and Seyyed Hossein Nasr, who advocate for an educational foundation based on tawhidi epistemology. The study ultimately calls for a fundamental reorientation of Islamic education away from imitation and toward an emancipatory system that integrates Divine revelation with human intellect and empirical experience.